2017
DOI: 10.1097/ta.0000000000001655
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism after major venous injuries: Competing priorities

Abstract: Therapeutic/care management, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…However, long-term bed rest leads to reduced muscle pumping, severe local blood ow stagnation, and serious vascular endothelial injury. Moreover, the accumulation of coagulation factors leads to the overactivation of the coagulation system, thereby leading to accelerated thrombosis [9,[13][14][15] . However, once the venous thrombosis of lower extremities is formed, due to changes in the body position or local massage factors, the thrombosis tends to fall off and form fatal PE; it has been reported that 10% of patients with DVT develop fatal PE [16] .…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term bed rest leads to reduced muscle pumping, severe local blood ow stagnation, and serious vascular endothelial injury. Moreover, the accumulation of coagulation factors leads to the overactivation of the coagulation system, thereby leading to accelerated thrombosis [9,[13][14][15] . However, once the venous thrombosis of lower extremities is formed, due to changes in the body position or local massage factors, the thrombosis tends to fall off and form fatal PE; it has been reported that 10% of patients with DVT develop fatal PE [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the studies looked at a range of different locations that were affected by the trauma. There were 4 studies that exclusively looked at lower limb trauma [20][21][22][23] whilst 3 looked at both upper and lower [24][25][26]. However, one study did not make clear distinctions between anatomical locations of the traumatic insult [27].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It would appear that the majority of studies looked at included patients suffering from vascular trauma alongside associated fractures although in some studies, it was difficult to determine the exact injuries. However, in two of the studies, they included patients suffering from head injuries with vascular trauma and fractures [21,24] but it is unclear if there was a difference in treatment protocol and outcomes with these patients alone. Notably, there were no identifiable studies on the effect of solely administering anti-platelet therapy on the outcomes of vascular trauma surgery.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The National Trauma Data Bank (NTDB) has the benefit of a large sample size of >4 million patient records from >700 facilities, representing every type of trauma center from large to small, and is the largest aggregation of U.S. and Canadian trauma registry data available. 2 This benefit is inherently balanced by its lack of granularity of the data. The NTDB does not provide data about intraoperative anticoagulation.…”
Section: Replymentioning
confidence: 99%